Dielectric spectroscopy of PVA/GO/FeGaInS4 hybrid films: thermal and compositional effects - Addayeva, Zeynab; Muradov, Mustafa; Niftiyev, Namiq; Mammedov, Faiq; Eyvazova, Goncha; Coskuner Filiz, Bilge (SPRINGER, 2025)
This work investigates the dielectric behavior of polyvinyl alcohol (PVA)-based nanocomposites incorporating FeGaInS4 crystals and varying amounts of graphene oxide (GO). The prepared samples include neat PVA, PVA with 2 wt.% FeGaInS4, and composites containing 1-3 wt.% GO in addition to 2 wt.% FeGaInS4. Measurements were conducted across a temperature range of 293-373 K and frequencies from 120 Hz to 1 MHz. Results showed that dielectric permittivity rose with increasing temperature and decreased with frequency. The dielectric loss (tan delta) was found to decline with higher GO content, while it generally increased with temperature-exhibiting a peak for the 3 wt.% GO sample between 333 and 373 K, attributed to relaxation phenomena. Electrical conduction characteristics, analyzed using the Correlated Barrier Hopping (CBH) model at 5 kHz, revealed that GO strongly influences conductivity, charge carrier density, and activation energy. A reduction in activation energy upon GO incorporation indicates improved charge transport. Overall, these findings suggest that tuning the GO content provides an effective strategy to modify dielectric and conduction properties, highlighting the potential of these nanocomposites in electronic device applications.
Keywords: GRAPHENE OXIDE; NANOCOMPOSITES; REDUCTION; MECHANISM; PVA; Materials Science